Strategi Penanganan Pembiayaan Bermasalah di Bank Syariah - Zahratunnisa, Zahratunnisa; Sari, Khofifah Indar Mawar; Fahira, Jeby (JIOSE: Journal of Indonesian Sharia Economics, 2023)
Sharia banks in Indonesia are currently experiencing significant developments, these developments must be followed by regulations and good banking management, including handling problem financing. It is undeniable that the financing business in Islamic banking has the potential to experience financing problems. The greater the problematic financing faced by banks, will reduce the soundness level of Islamic banks, decrease the quality of financing and the soundness of banks affect financial liquidity and solvency, which can ultimately affect the trust of depositors and even prospective customers. Not only that, the greater the amount of non-performing financing, the greater the amount of costs for reserve funds that must be provided so that it has a negative impact on profitability, because the losses borne by the bank will reduce profits which ultimately have a negative impact on Islamic bank capital. Related to this, this research was conducted using a qualitative method to analyze the factors that cause problem financing, as well as strategies for preventing and resolving problem financing in Islamic banks and finally being able to provide information to all parties, especially Islamic bank practitioners, about ways or strategies for handling and also solving problem financing.